2022
DOI: 10.3390/nu14091964
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity and the Association between Perceptions and Trust of Food Advertisements and Consumption of Ultra-Processed Foods among U.S. Parents and Adolescents

Abstract: Adolescents exposed to food and beverage advertisements (FBAs) typically low in nutrient density can be influenced in their food choices, eating behaviors, and health. This study examines the association between perceptions and trust of FBAs (key predictor) and the outcome of daily consumption of ultra-processed foods (UPFs) in parent-adolescent dyads, with risk of food insecurity as a potential moderator. Cross-sectional data from the Family, Life, Activity, Sun, Health and Eating (FLASHE) study was used to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…All studies controlled for SES indicators, but not access to healthy nutritious food or food insecurity specifically. Food insecurity is associated with higher UPF consumption [21] and a recent epidemiological survey study estimates participants with the highest UPF consumption have a 60% higher prevalence of food insecurity (RR = 1.60) [22]. Food insecurity is associated with elevated obesity risk in a previously published meta-analysis (OR = 1.53 ~RR 1.42) [23] and effects appear similar when examined prospectively in studies [24].…”
Section: Potential Unmeasured Confoundingmentioning
confidence: 83%
“…All studies controlled for SES indicators, but not access to healthy nutritious food or food insecurity specifically. Food insecurity is associated with higher UPF consumption [21] and a recent epidemiological survey study estimates participants with the highest UPF consumption have a 60% higher prevalence of food insecurity (RR = 1.60) [22]. Food insecurity is associated with elevated obesity risk in a previously published meta-analysis (OR = 1.53 ~RR 1.42) [23] and effects appear similar when examined prospectively in studies [24].…”
Section: Potential Unmeasured Confoundingmentioning
confidence: 83%
“…However, this association changes when food insecurity is taken into consideration. Chiong and Figueroa also found that parents with a higher level of education are more likely to explore advertised food products, which increases their children’s consumption of these products [ 25 ]. This implies that several risk factors associated with advertised food and beverage consumption contribute to health issues among children.…”
Section: Discussionmentioning
confidence: 99%
“…All studies controlled for SES indicators, but not access to healthy nutritious food or food insecurity specifically. Food insecurity is associated with higher UPF consumption (24) and a recent epidemiological survey study estimates participants with the highest UPF consumption have a 60% higher prevalence of food insecurity (RR = 1.60)(25). Food insecurity is associated with elevated obesity risk in meta-analysis (OR = 1.53 ∼ RR 1.42) (26) and effects appear similar when examined prospectively (27).…”
Section: Introductionmentioning
confidence: 99%